(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
Il contributo, sottoposto a valutazione, è destinato agli Studi in onore del prof. Mario Tedeschi, di prossima pubblicazione SOMMARIO: 1. Un problema pratico di libertà religiosa: le benedizioni pasquali nella scuola pubblica - 2. Le benedizioni pasquali a scuola nella recente giurisprudenza - 3. La laicità inclusiva della scuola pubblica italiana - 4. La benedizione pasquale in orario extrascolastico e la funzione della scuola come centro di promozione culturale, sociale e civile - 5. Fattore religioso e scuola pubblica nella legislazione scolastica - 6. La garanzia della libertà religiosa nelle comunità segreganti. Religious freedom in public schools. The little querelle over Easter Blessings ABSTRACT: This paper examines the current issue concerning the Easter Blessings imparted by a catholic priest in public schools in Italy. According to an old tradition dating back to the past but still followed by many parents, in some schools, especially primary ones, this brief rite usually takes place before Eastern. The majority of parents must agree on having it and it must be scheduled out of lessons time. Moreover, participation is very free for pupils, parents and teachers. A recent case law has challenged this practice, claiming that it would infringe the principle of secularism proper to public schools. This paper deals with the issue in the light of constitutional principles and the Italian legal framework. It focuses on the importance to keep a balance between secularism and religious freedom in public schools, where nowadays an increasing number of children stay for the whole day when both parents are at work.